Effect of surfactant self-assembly on lubrication performance in oil-based systems: the role of reverse micelles and vesicles - Gu, Haiyang; Hirayama, Tomoko (Frontiers in Mechanical Engineering, 2025)
Surfactants are effective additives for oil-based lubricants, capable of reducing friction under boundary lubrication conditions through their self-assembly into nanostructures. Understanding the relationship between their self-assembled structures and lubrication properties is essential for optimizing performance. In this study, the aggregation behavior of C12E4 in dodecane and its effects on friction and anti-wear properties were investigated. The results showed that C12E4 formed small reverse micelles at lower water concentrations, transitioning to larger reverse vesicles at higher concentrations. Elevated temperatures caused vesicle collapse, leading to the formation of smaller aggregates. Small reverse micelles effectively reduced friction and wear, while larger vesicles increased friction due to their obstructive effect. At higher temperatures, friction coefficients converged as reverse vesicles ruptured under shear. Neutron reflectometry (NR) revealed a strong correlation between the density of the adsorbed layer and frictional properties. As a powerful technique, NR enables direct, nanometer-scale characterization of adsorption layers formed by lubricant additives at solid–liquid interfaces, providing critical insights into the structural basis of lubrication performance. These findings underscore the pivotal role of surfactant self-assembly in oil-based lubrication and highlight the importance of optimizing water content and temperature to achieve effective friction reduction. They offer valuable guidance for developing surfactant-based lubricant additives, particularly for enhancing boundary lubrication performance under high-load and high-temperature industrial conditions.